2005
DOI: 10.1007/s00439-005-1285-0
|View full text |Cite
|
Sign up to set email alerts
|

Functional promoter polymorphism in the TBX21 gene associated with aspirin-induced asthma

Abstract: Asthma is a phenotypically heterogeneous disorder with many etiologic factors and clinical characteristics. T-bet, a Th1-specific transcription factor of T-box family, has been found to control interferon-gamma (IFN-gamma) expression in T cells. Mice lacking the T-bet gene (tbx21) demonstrate multiple physiological and inflammatory features reminiscent of human asthma. In order to examine whether polymorphisms in the candidate gene, TBX21, located on chromosome 17q21.32, are related to the risk of human asthma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 50 publications
2
68
1
Order By: Relevance
“…Ylikoski and colleague also reported that TBX21 polymorphisms were not related to a Finnish asthmatic population (Ylikoski et al, 2004). A study on a Japanese population demonstrated the associations of one TBX21 polymorphism with aspirin-induced asthma, but not with other forms of asthma (Akahoshi et al, 2005). Raby and colleague recently demonstrated that TBX21 polymorphisms were associated with asthma and airway hyperresponsiveness in a North American population (Raby et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Ylikoski and colleague also reported that TBX21 polymorphisms were not related to a Finnish asthmatic population (Ylikoski et al, 2004). A study on a Japanese population demonstrated the associations of one TBX21 polymorphism with aspirin-induced asthma, but not with other forms of asthma (Akahoshi et al, 2005). Raby and colleague recently demonstrated that TBX21 polymorphisms were associated with asthma and airway hyperresponsiveness in a North American population (Raby et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Susceptibility to asthma and airway hyper-responsiveness in asthmatic children has been associated with upstream SNPs in the TBX21 gene (Raby et al, 2006), and an SNP in the promoter region has been associated with aspirin-induced asthma in Japanese asthmatics. The latter SNP, with involves a substitution of a tyrosine with a cystein, leads to increased transcriptional activity of TBX21 (Akahoshi et al, 2005). Polymorphisms in TBX21 may be of importance in the treatment of asthma, since an SNP in TBX21 has been shown to enhance the effects of inhaled corticosteroid treatment in asthmatic children (Tantisira et al, 2004).…”
Section: Migrationmentioning
confidence: 99%
“…13 Taking into consideration the essential role of T-bet in Th1 responses development, the TBX21 (17q21.32) -1993T/C polymorphism (rs4794067) of the promoter region of T-bet gene has been associated with an increased binding affinity to Sp1 transcription factor and increased transcriptional activity of the TBX21 gene, resulting in a predisposition to a Th-1 biased immune response characterized by increased IFN-g secretion. 17,18 Indeed, numerous studies have associated the TBX21-1993T/C SNP with increased risk or early onset of different diseases, such as type I autoimmune hepatitis, 19 systemic lupus erythematosus, 18 childhood asthma 20 and aspirin-induced asthma. 17 Despite the previous association of Th1-type responses with periodontitis development, no study has investigated the possible influence of this SNP in periodontitis, although it has a potential functional influence in Th1-polarization.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Indeed, numerous studies have associated the TBX21-1993T/C SNP with increased risk or early onset of different diseases, such as type I autoimmune hepatitis, 19 systemic lupus erythematosus, 18 childhood asthma 20 and aspirin-induced asthma. 17 Despite the previous association of Th1-type responses with periodontitis development, no study has investigated the possible influence of this SNP in periodontitis, although it has a potential functional influence in Th1-polarization.…”
Section: Introductionmentioning
confidence: 99%